2000
DOI: 10.1016/s0925-4773(00)00318-x
|View full text |Cite
|
Sign up to set email alerts
|

XSIP1, a Xenopus zinc finger/homeodomain encoding gene highly expressed during early neural development

Abstract: We have isolated a Xenopus homologue of the zinc finger/homeodomain-containing transcriptional repressor Smad-interacting protein-1 (SIP1) from mouse. XSIP1 is activated at the early gastrula stage and transcription occurs throughout embryogenesis. At the beginning of gastrulation, XSIP1 is strongly expressed in prospective neurectoderm. At the neurula stage, XSIP1 is highly expressed within the neural plate but weakly in the dorsal midline. At later stages of development transcripts are detected primarily wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 15 publications
1
35
0
Order By: Relevance
“…In line with our observations, SIP1 expression has been associated with migratory and invasive mechanisms occurring during embryonic development. Indeed, a high level of SIP1 has been detected during the formation of the neural tube and this has been shown to play a key role in the migration of neural crest cells (Eisaki et al, 2000;van Grunsven et al, 2000;, a system largely described as a physiological archetypal model of EMT (Duband et al, 1995;Tucker, 2004). Also, an increased expression of SIP1 has been described in NMuMG cells which have undergone a TGFβ1-induced EMT characterized by decreased E-cadherin expression and increased N-cadherin expression (Maeda et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In line with our observations, SIP1 expression has been associated with migratory and invasive mechanisms occurring during embryonic development. Indeed, a high level of SIP1 has been detected during the formation of the neural tube and this has been shown to play a key role in the migration of neural crest cells (Eisaki et al, 2000;van Grunsven et al, 2000;, a system largely described as a physiological archetypal model of EMT (Duband et al, 1995;Tucker, 2004). Also, an increased expression of SIP1 has been described in NMuMG cells which have undergone a TGFβ1-induced EMT characterized by decreased E-cadherin expression and increased N-cadherin expression (Maeda et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The first studies on ZEB2/SIP1 mRNA expression were performed in Xenopus embryos and indicated an important role in early embryogenesis. XSIP1 mRNA is first detected at stage 10.5 (early gastrula) in Xenopus embryos, primarily in dorsal mesoderm and ectoderm [67]. During gastrula and neurula stages, expression persists in neuroectoderm, the neural folds, neural tube, migrating neural crest and lateral plate mesoderm.…”
Section: Key Roles Of Zeb Family Members In Developmentmentioning
confidence: 99%
“…From early tail bud stage on, XdEF1 and XSIP1 are coexpressed in the migratory cranial neural crest, retina and neural tube. In the adult, XSIP1 mRNA is detected in organs derived from ectodermal, mesodermal and endodermal origin, including brain, spinal cord, eye, skin, heart, liver and lung [67]. XSIP1 is known to play an important role in the regulation of Xbra (Xenopus Brachyury), a member of the T-box family of transcription factors and essential in mesoderm formation during early development.…”
Section: Key Roles Of Zeb Family Members In Developmentmentioning
confidence: 99%
“…Smad proteins are signal inducers involved in the TGF-b signaling cascade. XSIP1, the Xenopus homologue of ZFHX1B, is expressed throughout embryogenesis, initially highly expressed in the prospective neuroectoderm and later within the dorsal neural tube and neural crests [van Grunsven et al, 2000]. In early human embryos, ZFHX1B is expressed in neural crest derived cells, including enteric nervous system and the facial neuroectoderm, and the central nervous system, genital tubercle and kidneys [Espinosa-Parrilla et al, 2002].…”
Section: Mutations and Genotype: Phenotype Correlationsmentioning
confidence: 99%